Expert Consensus on Rare Disease Pharmaceutical Care in Hospitals (2025) - Rare Disease Drug Committee of the Chinese Pharmaceutical Association (Xiehe Yixue Zazhi)
In recent years, with strong support from the national government, the diagnosis and treatment of rare diseases in China have achieved significant progress. However, only 5% of rare diseases worldwide have effective treatments, and poor drug accessibility remains a major challenge in the field of rare diseases, both in China and globally. Due to limited research data, insufficient clinical experience, and a lack of medication expertise, there is an urgent need for pharmacists to play an expanded role throughout the rare disease care process, alongside the establishment of systematic management and monitoring systems. To enhance the leading role of medical institutions in securing rare disease drug availability, improve pharmaceutical care quality, standardize service content and delivery models, and fully leverage pharmacists' expertise in rare disease management, the Rare Disease Drug Committee of the Chinese Pharmaceutical Association organized a panel of experts to develop the Expert Consensus on Rare Disease Pharmaceutical Care in Hospitals (2025). This consensus aims to establish a standardized pharmaceutical care framework tailored to China's healthcare context, ensuring the accessibility, appropriateness, efficacy, and safety of rare disease treatments.